CRIANÇAS INDÍGENAS DO LARANJEIRA NHANDERU: O APRENDER E O SER CRIANÇA KAIOWÁ EM UMA ÁREA DE RETOMADA - Tania Milene Nugoli Moraes (2022)
The present study had the general objective of understanding how Kaiowá children contribute to the thinking and doing of their culture, based on their life experience and the reflections they construct while living in the Laranjeira Nhanderu recovery area, located in the municipality of Rio Brilhante, in the State of Mato Grosso do Sul. Using participant observation, an anthropological method par excellence, as well as the literature review relevant to the theme, I understood that reciprocity and beautiful words, components of traditional Kaiowá indigenous education, form individuals, at the same time that they help them to reflect on their lives and to propose new readings, in the light of these teachings, about the events that affect them, and the Kaiowá children also contribute to this movement.